Obesity, sedentary lifestyle, and exhaled nitric oxide in an early adolescent cohort. Issue 2 (5th December 2019) - Flashner, Bess M.; Rifas‐Shiman, Sheryl L.; Oken, Emily; Camargo, Carlos A.; Platts‐Mills, Thomas J.; Workman, Lisa; Litonjua, Augusto A.; Gold, Diane R.; Rice, Mary B.
Abstract: Fractional exhaled nitric oxide (FeNO) is a marker of airway inflammation that is well‐characterized in allergic disease states. However, FeNO is also involved in nonallergic inflammatory and pulmonary vascular mechanisms or responses to environmental stimuli. We sought to determine the extent to which obesity or sedentary lifestyle is associated with FeNO in adolescents not selected on the basis of allergic disease. In Project Viva, a prebirth cohort study, we measured body mass index (BMI), skinfold thicknesses, waist circumference, body fat, hours watching television, hours of physical activity, and heart rate after exercise among 929 adolescents (median age, 12.9). We measured FeNO twice and averaged these as a continuous, log‐transformed outcome. We performed linear regression models, adjusted for child age, sex, height, and race/ethnicity, maternal education and smoking during pregnancy, household income and smoking, and neighbourhood characteristics. In secondary analysis, we additionally adjusted for asthma. More than 2 hours spent watching TV was associated with 10% lower FeNO (95% confidence interval [CI]: −20, 0%). Higher body fat percentage was also associated with lower FeNO. After additional adjustment for asthma, teens who are underweight (BMI <5th %tile, 3%) had 22% lower FeNO (95%CI: −40, 2%) and teens who are overweight (BMI ≥85th %ile, 28%) had 13% lower FeNO (95%CI: −23, −2%). Each of these associations of lifestyle and body weight with lower FeNO were greater in magnitude after adjusting for asthma. In summary, sedentary lifestyle, high and low BMI were all associated with lower FeNO in this adolescent cohort.